Switched-Capacitor-Based Five-Level T-Type Inverter (SC-5TI) with Soft-Charging and Enhanced DC-Link Voltage Utilization - Lee, Sze Sing; Siwakoti, Yam; Barzegarkhoo, Reza; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2021)
The emerging switched-capacitor-based multilevel inverters offer interesting merits such as self-balancing of capacitor voltages and boosting of voltage gain. While the switched capacitors (SCs) in these topologies are charged in parallel with the dc source, severe current spikes issue is inevitable, rendering them impractical at high power. This article proposes a novel switched-capacitor-based T-type inverter that mitigates the current spikes by enabling soft charging for its integrated SCs, where both SC in the topological structure charges through a dedicated circuit comprises of an inductor and two switches. The proposed topology is capable of five-level ac voltage generation and when compared to a classical T-type/ANPC (active neutral-point-clamped) inverter, it achieves higher dc-link voltage utilization since its maximum attainable voltage gain is doubled. Theoretical findings of the proposed topology are validated by both the simulation and experimental results.
Keywords: Active neutral point clamped; Capacitor voltages; Current spikes; DC-link voltages; Multilevel inverter; Self-balancing; Switched capacitor; Topological structure; Five level; multilevel inverter; soft charging; switched capacitor (SC); T-type inverter